2017
DOI: 10.1016/j.pnpbp.2017.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic inhalation of electronic cigarettes containing nicotine on glial glutamate transporters and α-7 nicotinic acetylcholine receptor in female CD-1 mice

Abstract: Alteration in glutamate neurotransmission has been found to mediate the development of drug dependence, including nicotine. We and others, through using western blotting have reported that exposure to drugs of abuse reduced the expression of glutamate transporter-1 (GLT-1) as well as cystine/glutamate antiporter (xCT), which consequently increased extracellular glutamate concentrations in the mesocorticolimbic area. However, our previous studies did not reveal any changes in glutamate/aspartate transporter (GL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(76 citation statements)
references
References 80 publications
(120 reference statements)
2
74
0
Order By: Relevance
“…Although continuous five-week EtOH consumption reduced GLT-1 expression in the HIP (Aal-Aaboda et al, 2015), we did not observe any changes in GLT-1 expression in the HIP following binge-like drinking of EtOH with or without NIC using a limited access procedure. A previous study reported that phasic exposure to electronic cigarettes (i.e., vapors-containing NIC) for six months did not reduce GLT-1 in the HIP (Alasmari et al, 2017).…”
Section: Accepted Manuscript 17mentioning
confidence: 92%
“…Although continuous five-week EtOH consumption reduced GLT-1 expression in the HIP (Aal-Aaboda et al, 2015), we did not observe any changes in GLT-1 expression in the HIP following binge-like drinking of EtOH with or without NIC using a limited access procedure. A previous study reported that phasic exposure to electronic cigarettes (i.e., vapors-containing NIC) for six months did not reduce GLT-1 in the HIP (Alasmari et al, 2017).…”
Section: Accepted Manuscript 17mentioning
confidence: 92%
“…Rapid growth in consumption is fueled in large part due to successful social media-based marketing and availability of appealing flavors and sleek devices. Although a large focus of research and regulation has been on the nicotine delivery function of these devices, because of the high addictiveness and known adverse health effects of nicotine, the majority of e-liquids contain propylene glycol (PG), glycerol (Gly), flavorants and contaminants, all of which may cause their own adverse effects on health (3)(4)(5)(6)(7)(8). Regardless of chemicals contained, the popularity of e-cigarettes is driven, in part, by the notion that e-cigarettes represent a riskfree alternative to combustible cigarettes, and hence, few regulations exist to control the quality and composition of the ingredients used in e-cigarettes (7,9).…”
Section: Introductionmentioning
confidence: 99%
“…The suggestion therefore is that a proportion of these CS effects are influenced by components of CS that are not present in EC aerosol. Alasmari et al (2017Alasmari et al ( , 2019 also found that 6 month EC exposure, giving plasma nicotine levels comparable to heavy smokers, increased α7nAchR, a major presynaptic nicotinic receptor in glutamatergic neurons, in frontal cortex (FC) and striatum (STR) but not hippocampus. This increase in α7nAchR was accompanied by decreased glutamate transporter expression in STR and decreased cysteine/glutamate antiporter in both STR and hippocampus.…”
Section: What Are the Adverse Effects Of E-cigarettes?mentioning
confidence: 96%
“…Many groups have measured cotinine, the more metabolically stable metabolite of nicotine, in blood and urine for comparison with human exposure levels. In four studies that quantified urinary cotinine, three had levels indicative of heavy smoking (McGrath-Morrow et al 2015;Ponzoni et al 2015;Lauterstein et al 2016) and one of light smoking (Olfert et al 2018), while studies measuring serum (Smith et al 2015;Sussan et al 2015;Garcia-Arcos et al 2016;Alasmari et al 2017;Laube et al 2017;Rau et al 2017;Chen et al 2018a;Crotty Alexander et al 2018) or plasma (McGrath-Morrow et al 2015;Qasim et al 2018;Espinoza-Derout et al 2019a) cotinine levels (range 9-611 ng ml −1 ) were equivalent to the range observed in active smokers (Hukkanen et al 2005). Of course, not all e-liquids contain nicotine and the nicotine content of e-liquids employed in animal studies has varied from 12 to 33 mg ml −1 (Table 1).…”
Section: Exposure Models and Dosementioning
confidence: 99%